2015
DOI: 10.1016/j.rpor.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

SIMBOSPROST: Prevalence of metabolic syndrome and osteoporosis in prostate cancer patients treated with radiotherapy and androgen deprivation therapy: A multicentre, cross-sectional study

Abstract: a b s t r a c tAim: To assess the prevalence of metabolic syndrome (MetS) and osteoporosis in patients with prostate cancer (PCa) treated with radical radiotherapy (RT) with or without androgen deprivation therapy (ADT).Background: Worldwide, the prevalence of MetS is estimated to range from 20% to 25% of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…50 Male hypogonadism is an independent risk factor for metabolic syndrome, while low testosterone and SHBG levels can predict metabolic syndrome in men. 51,52 Additionally, as mentioned above, ADT causes a high degree of alteration in the metabolic parameters and thus it is possible that ADT increases the risk of metabolic syndrome. Indeed, some studies have shown that about 36-55% of men receiving ADT for more than a year will develop metabolic syndrome, independent of age, race, and stage of PCa.…”
Section: 49mentioning
confidence: 98%
“…50 Male hypogonadism is an independent risk factor for metabolic syndrome, while low testosterone and SHBG levels can predict metabolic syndrome in men. 51,52 Additionally, as mentioned above, ADT causes a high degree of alteration in the metabolic parameters and thus it is possible that ADT increases the risk of metabolic syndrome. Indeed, some studies have shown that about 36-55% of men receiving ADT for more than a year will develop metabolic syndrome, independent of age, race, and stage of PCa.…”
Section: 49mentioning
confidence: 98%
“…A US study of 2290 patients with prostate cancer found that only 197 (8.6%) underwent DXA scanning within one year before, and six months after starting ADT [ 17 ]. A smaller Spanish study found that 62% (168/270) of patients on ADT underwent DXA scanning [ 32 ]. The high level of DXA testing at our centre may have been due to the efforts of a small group of clinicians with heightened awareness of the deleterious effects of ADT on bone health in the setting of accessible DXA scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer patients treated with radiotherapy combined with adjuvant hormonal therapy, regardless of the length of treatment, are twice more likely to be diagnosed with the metabolic syndrome than patients treated with radiotherapy alone [10].…”
Section: Metabolic Complications Of Hormonal Therapymentioning
confidence: 99%